Xanthomatous hypophysitis causing hypogonadotropic hypogonadism resulting in delayed presentation of slipped capital femoral epiphysis. (4th March 2022) - Singh, Kirit; Kanodia, Avinash Kumar; Ross, Peter; Torgersen, Antonia; Maclean, Jamie; Leese, Graham; Hossain-Ibrahim, Kismet
Abstract: An 18-year-old man who underwent bilateral pinning of his hip joints after a left unstable Slipped Capital Femoral Epiphysis (right pinned prophylactically) was noted to have delayed secondary sexual characteristics and post-operative diabetes insipidus. The patient also described a history of fatigue, headache and polydipsia for the past 4 years. Endocrine investigations revealed reduced androgen levels, hypocortisolism, a borderline normal Serum ACE and secondary hypothyroidism. Magnetic Resonance Imaging of the pituitary gland identified an enhancing mass and a thickened stalk which trans-nasal endoscopic biopsy found to be necrotic with pus. Histology confirmed a diagnosis of Xanthomatous Hypophysitis, an inflammatory condition likely related to a partial rupture of a Rathke cleft cyst. The patient was subsequently commenced on Androgen, Thyroxine, Desmopressin and Hydrocortisone therapy with on-going endocrine follow-up. Although endocrine dysfunction & hypogonadism has been recognised to be a risk factor for SCFE at an atypically older age, due to reduced androgen levels leading to a weakened physeal plate, this is the first known case of a Xanthomatous Hypophysitis resulting in pituitary dysfunction and eventual SCFE. This case highlights that an increased range of pituitary disorders should be considered in late presentations of SCFE; and vice versa the risk of SCFE should be considered in patients with prolonged hypogonadotropic hypogonadism.